Navigating the Uncanny Spaces: Spatial Relations in Don DeLillo’s Falling Man - Gaj Tomaš ([sic])
Following the twentieth-century’s spatial turn in literary and cultural studies, this paper examines spaces and spatiality in Don DeLillo’s novel Falling Man, a seminal fictional response to the most traumatic (spatial) event in the USA at the turn of the century. Starting from Robert T. Tally Jr.’s thesis that authors are cartographers, I analyze how DeLillo acts as a mapper of the post-9/11 space. By exploring the depictions of the altered spatial landscape DeLillo creates, and the world he thrusts his characters into, I examine the intricate relationship between space and identity. Ultimately, I argue that the loss of a familiar and dependable space creates unfamiliar spaces the characters struggle to navigate.Keywords: space, spatiality, DeLillo, Falling Man, 9/11, post-9/11 literatureIn the introduction to his 2013 book Spatiality, Robert T. Tally Jr. claims that “over the past few decades, spatiality has become a key concept for literary and critical studies” (3). Exploring the different disciplinary takes on spatiality – literary cartography, geography, and geocriticism – Tally asserts that if the nineteenth century’s major obsession was dominated by the discourses of time and history, in the post-war period of the twentieth century, “space began to reassert itself in critical theory, rivaling if not overtaking time in significance” (3). The author reiterates numerous writers, philosophers, and thinkers who came before him to suggest there has been the so-called spatial turn. Bertrand Westphal, the founder of geocriticism, a literary theory that incorporates the study of geographic space, claims that “cataclysmic restructuring of societies during, and in the immediate aftermath of, Second World War, led to the decline in the obsession with time” (Tally 6). In the essay “Of Other Spaces,” French philosopher Michel Foucault argues that we live in the world “when our experience of the world is less that of a long life developing through time than that of a network that connects points and intersects with its own skein” (22). He argues that the twentieth-century era is the epoch of space and that “we are in the epoch of juxtaposition, the epoch of the near and far, of the side-by-side, of the dispersed” (Foucault and Miskowiec 22).